Scaling up a one-health model of conservation through public health: experiences in Uganda and the Democratic Republic of the Congo - Gladys Kalema-Zikusoka, MsPVM; Joseph Byonanebye, PhD (Elsevier, 2019)
Background: Endangered mountain gorillas are threatened by habitat destruction, wildlife poaching, and disease-factors exacerbated by high levels of human poverty and population growth rates in and around Bwindi Impenetrable National Park in Uganda. In 2003, Conservation Through Public Health (CTPH) was founded when fatal scabies skin disease outbreaks in Bwindi gorillas were traced to local communities who had inadequate access to basic health services. In 2007, CTPH implemented volunteer community-based family planning and later trained village health and conservation teams. These teams, using the one-health approach, promoted family planning, health, and conservation. The work resulted in a three-fold increase in family-planning users, reduced incidence of gorilla disease, and greater community support for conservation. Further, women become more involved in conservation and men become more involved in family planning. Here, we describe the scaling up of the one-health approach to protected areas in Africa. Methods: In 2015, CTPH expanded the model of village health and conservation teams, sustained by village savings and loan associations, to a protected area with gorillas, at Mikeno and Mount Tshiabirimu sectors of Virunga National Park, Democratic Republic of the Congo, and to a non-protected gorilla area in Bukwo, Kween, and Bulambuli Districts of Mount Elgon National Park, Uganda. Both areas have high poverty levels and human population densities. Staff from CTPH monitored the project; village health and conservation teams collected data at household level. Findings: Between 2015 and 2017, 81 000 people from 13 000 households in 139 villages in five districts were reached by 163 village health and conservation teams. Teams established ten financially stable networks that had group livestock to generate income that was reinvested in Village Savings and Loan Associations. Some households had improved water sanitation and hygiene, and 1597 patients with scabies were referred to the nearest health centre, as were 35 people with tuberculosis and 1674 with malnutrition. There was also an uptake of family planning services, including: implants (571 people), the contraceptive pill (479), intrauterine devices (119), tubal ligation (163), and side-effects management (749). At Mount Elgon, 9652 homes planted trees. Contraceptives from the Ministry of Health in Uganda, were provided free of charge to 3829 people in Mount Elgon and 285 people in Virunga. Interpretation: CTPH's one-health approach has promoted better family planning, population, health, and conservation in Uganda and the Democratic Republic of the Congo. Scaling up requires more resources and dedicated organisational, governmental, professional, and community collaborations. Funding: Global Development Network Japanese Social Development Fund.